The Role of Alternative Investments in the Development of Capital Markets in Terms of the Transformation of Georgia with the EU - George Abuselidze (Proceedings of the 4th International Conference on European Integration 2018, 2018)
In the modern economy investmentplays an important role. Investment diversification ensures the development of various markets, including the development of the capital market, which depends on the socio-economic situation of the country and the financial policy. Therefore, it is important to review Georgia's, as a post Soviet country's capital (loan) market with State Securities, which is an important area of alternative investment.According to Georgia-EU Deep and Comprehensive Free Trade Area Agreement (DCFTA) Georgia has taken the obligation to make capital market compatible with the EU market, including the possibility of forming alternative investments and prospects for its development. Therefore, it is important to conduct a comparative analysis with the country of similar data with Georgia within the EU and reveal the possibility of alternative investments development and the supportive factors that may affect the decision of the potential investor.
Keywords: E20; E22; E27; E44; 330; alternative investments; association agreement; EU capital market; eurobonds; inflation; state securities